2173. Co-Occurring Dysphagia and Frailty are Common and Associated with Increased Disease Severity in Older Adults Presenting with Community-Acquired Pneumonia. (15th December 2022) - Pulia, Michael; Robison, Raele; Schwei, Rebecca; Gustafson, Sara; Broghammer, Charles; Herrin, Rachelle; Rogus-Pulia, Nicole
Abstract: Background: Impaired swallowing (dysphagia) and physical (frailty) function are associated with community-acquired pneumonia (CAP), however, neither are routinely screened for in patients with CAP. We sought to: 1) examine frailty and dysphagia screening profiles in a cohort of older adults with CAP; and 2) determine if these screening profiles differ across CAP severity levels. Methods: Older adults (≥65) meeting diagnostic criteria for pneumonia are included as participants. During the index encounter, dysphagia (3-ounce water swallow) and frailty (FSQ;4 ≥3 = frailty) screeners are administered. Thirty days post-enrollment, a standardized clinical severity scale is used to document CAP severity (mild (ambulatory management); moderate-severe (hospitalization)). Statistical analysis included descriptives and cross tabulations. Results: We enrolled 26 participants (13 female) with a mean age of 73 (SD: 7.1). Nine (34.6%) and 17 (65.4%) patients had mild and moderate-severe CAP severity, respectively. Twenty (76.9%) and 14 (53.8%) patients met screening criteria for dysphagia and frailty, respectively. Screening profiles included: no frailty or dysphagia (15.4%), frailty and no dysphagia (11.5%), no frailty but dysphagia (30.8%), frailty and dysphagia (42.3%). No frailty but dysphagia (44.4%) was the most common mild CAP severity profile. When CAP severity worsened (moderate-severe), co-occurring frailty and dysphagia was most prevalent (47.1%). Fig. 1. Combined dysphagia and frailty screening profiles for this cohort. Dysphagia only was highly prevalent (31%), however, the majority of individuals presented with co-occurring dysphagia and frailty (42%). Fig. 2. Screening profiles across CAP severity levels. No frailty/dysphagia (44.4%) was the most common mild CAP profile. Co-occurring frailty/dysphagia was most prevalent (47.1%) in mod-severe CAP. Conclusion: In this cohort, standardized screenings for dysphagia and frailty revealed both were common and frequently co-occurred, particularly in the high acuity CAP group. These data suggest older adults with pneumonia may have underlying dysphagia and/or frailty that warrant further evaluation. These potential impairments should be considered in care pathways (e.g. antibiotic therapy and rehabilitation services consultation) to mitigate negative sequelae. Disclosures: All Authors : No reported disclosures.